2021
DOI: 10.1128/aem.00170-21
|View full text |Cite
|
Sign up to set email alerts
|

Coinducible Catabolism of 1-Naphthol via Synergistic Regulation of the Initial Hydroxylase Genes in Sphingobium sp. Strain B2

Abstract: 1-Naphthol, a widely used raw material for organic synthesis, is also a well-known organic pollutant. Due to its high toxicity, 1-naphthol is rarely used by microorganisms as the sole carbon source for growth. In this study, catabolism of 1-naphthol by Sphingobium sp. strain B2 was found to be greatly enhanced by additional supplementation with primary carbon sources (e.g., glucose, maltose and sucrose), and 1-naphthol was even used as the carbon source for growth when strain B2 cells had been pre-induced by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This interesting regulatory mechanism, which is similar to a double-lock switch, indicated that the catabolism of 1-naphthol is only initiated when the cells have a sufficient carbon source to maintain basic metabolism. 19 In this study, we demonstrated that CehC1C2 could catalyze 2-naphthol to produce 1,2-DHN and that 2naphthol could activate the transcription of the gene cluster. These results complemented the co-inducible catabolism of naphthol compounds by the cehC1C3C2/ndcA1BA2 cluster.…”
Section: Transcription Of Cehc1c2mentioning
confidence: 64%
See 3 more Smart Citations
“…This interesting regulatory mechanism, which is similar to a double-lock switch, indicated that the catabolism of 1-naphthol is only initiated when the cells have a sufficient carbon source to maintain basic metabolism. 19 In this study, we demonstrated that CehC1C2 could catalyze 2-naphthol to produce 1,2-DHN and that 2naphthol could activate the transcription of the gene cluster. These results complemented the co-inducible catabolism of naphthol compounds by the cehC1C3C2/ndcA1BA2 cluster.…”
Section: Transcription Of Cehc1c2mentioning
confidence: 64%
“…NdcS (CehR3) was predicted to be an activator that rapidly promoted the level of transcription of ndcA1BA2 ( cehC1C3C2 ) in the presence of 1-naphthol. This interesting regulatory mechanism, which is similar to a double-lock switch, indicated that the catabolism of 1-naphthol is only initiated when the cells have a sufficient carbon source to maintain basic metabolism . In this study, we demonstrated that CehC1C2 could catalyze 2-naphthol to produce 1,2-DHN and that 2-naphthol could activate the transcription of the gene cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…McbC, a one-component flavin-dependent monooxygenase identified from Pseudomonas sp. strain C4 ortho-hydroxylates 1-naphthol (an intermediate of the insecticide carbaryl and the herbicide napropamide) to 1,2-dihydroxynaphthalene (41,83,110) (Supplemental Figure 3h). Other structural analogs of 1-naphthol, such as 4-chloro-1-naphthol and 5-amino-1-naphthol, can also be hydroxylated by McbC.…”
Section: Ortho-hydroxylationmentioning
confidence: 99%